2014
DOI: 10.1002/tcr.201402057
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide‐Mediated Selective Cleavage of [60]Fullerene Skeleton Bonds: Towards the Synthesis of Open‐Cage Fulleroid C55O5

Abstract: Replacement of a pentagon in [60]fullerene with five oxygen atoms yields the open-cage compound C55O5 with five carbonyl groups on the rim of the orifice. Our attempts to synthesize such a target molecule starting from C60 have led us to prepare the fullerene-mixed peroxides such as C60(OO-t-Bu)6 with all the peroxo addends surrounding the same pentagon. Further investigations of the peroxide chemistry have generated various open-cage fullerene derivatives, including the carbon monoxide encapsulated endohedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…In ar esearch proposal back in 2000, Gan proposed the molecule 15 C 55 O 5 by replacing ap entagoni nC 60 with five oxygen atoms (Scheme 7). [14] Arrangemento ft he five carbonyl groups is reminiscent of the cucurbit [5]uril. Su et al performed DFT calculations for C 55 O 5 .…”
Section: Scheme5macrocycleligands-based On Bottom Up Synthesis Appromentioning
confidence: 99%
“…In ar esearch proposal back in 2000, Gan proposed the molecule 15 C 55 O 5 by replacing ap entagoni nC 60 with five oxygen atoms (Scheme 7). [14] Arrangemento ft he five carbonyl groups is reminiscent of the cucurbit [5]uril. Su et al performed DFT calculations for C 55 O 5 .…”
Section: Scheme5macrocycleligands-based On Bottom Up Synthesis Appromentioning
confidence: 99%
“…In conclusion, multiaddition is shown to be an effective method for separating the ellipsoidal C 70 p system into various fluorophores.T he octamethoxy adduct C 70 (OMe) 8 could be readily prepared on ag ram scale and is shown to be av ersatile precursor for selective functionalization as ar esult of the relatively stable fullerene C 70 ÀOMe bond and moderate steric hindrance from the OMe groups.T he emission wavelength of C 70 derivatives can be fine-tuned over awide range from blue to red. In addition, click reactions may be applied to attach functional groups to the fluorophore.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[8] In an effort to prepare C 70 open-cage derivatives,w ei nvestigated the reactivity of C 70 (OOtBu) 10 [9] and found that the peroxo groups in this compound show very poor selectivity in C 70 cage-opening reactions.W et hen turned our attention to the analogous methoxyl adducts C 70 (OMe) 8/10 with all the methoxyl groups located on the equatorial region. Theo ctaadduct C 70 (OMe) 8 was prepared by treating C 70 Cl 8 [10] with methanol in the presence of silver perchlorate in excellent yield (Scheme 1). Under similar conditions,t he decaadduct C 70 (OMe) 10 was obtained in moderate yield from C 70 Cl 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Recently, an iridium pyrrolidinofullerenec omplex was prepared [3e] and was shown to act as an effective hydrogen-transfer catalyst. [6] Selective cleavage of fullerene skeleton bondsw ithin al ocal area results in open-cagef ullerenes, [7] which could also form metal complexes with heteroatoms on edge of the structure. Due to the unique spherical p system, metal complexesw ith open-cage fullerene as ligandsa re attractive targets in order to explore potentiala pplications.…”
Section: Introductionmentioning
confidence: 99%